Simulation of human body dynamic response to crash loads. (5th August 2014) - Robbins, D.H.; Simic, D.
A review is given of the development of several crash victim simulation models. Applications of these models to various automotive safety problems are described based on the work of a number of uses both in the United States and Europe. It is concluded that crash victim simulation models can serve the automobile designer as a tool to reduce test costs when combined with well–conceived laboratory test programmes.